Speaking Skills Help in Propagating a Message Effectually - Shakuntala Yadav, Rakesh Gupta, Pragya Mishra, (European Economic Letters (EEL), 2023)
It has often been believed that speaking is a phenomenon which naturally gets inculcated within us but when we talk about formal speaking then we ought to be conscious while speaking anything. Having speaking skills meant having the talent to grab the listeners’ or audience’s attention towards us. There are certain parameters on which focus needs to be put on while speaking. According to Marriam Bashir et al.(2011), it is indeed true that speaking is not only the words of the speaker which matter but it is the overall components one needs to think about consisting of the speaker’s gesture, voice modulation, voice pitch, pace and most of all the pronunciation which takes the message in the correct direction instead of being encompassed with ambiguities. In today’s era, one must have good speaking skills to impart his/her knowledge so that the knowledge can be transmitted smoothly manually as well as technically via YouTube and other media sources. This paper is going to be one of the ammunition via which the speaker will be instilled with the required components to have a smoother and comprehending communication.